2002
DOI: 10.1200/jco.20.5.1375
|View full text |Cite
|
Sign up to set email alerts
|

Promising Survival for Patients With Newly Diagnosed Glioblastoma Multiforme Treated With Concomitant Radiation Plus Temozolomide Followed by Adjuvant Temozolomide

Abstract: Continuous daily temozolomide and concomitant radiation is safe. This regimen of concomitant chemoradiotherapy followed by adjuvant chemotherapy may prolong the survival of patients with glioblastoma. Further investigation is warranted, and a randomized trial is ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
285
2
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(305 citation statements)
references
References 0 publications
15
285
2
3
Order By: Relevance
“…About half of grade IV tumors (18 of 34) versus almost all grade III tumors (29 of 30) were treated with PCV (Table 1), raising the possibility that the observed difference between grades in the association Ap endo activity with TTP might reflect an association with PCV therapy rather than with tumor 7 For example, an HR of 1.06 indicates that a glioma with an Ap endo activity of 0.046 is 1.06 times more likely to progress at any moment in time than a glioma with an activity of 0.036, all other things being equal. Note, however, that a difference of 0.01 in activity is relatively small.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…About half of grade IV tumors (18 of 34) versus almost all grade III tumors (29 of 30) were treated with PCV (Table 1), raising the possibility that the observed difference between grades in the association Ap endo activity with TTP might reflect an association with PCV therapy rather than with tumor 7 For example, an HR of 1.06 indicates that a glioma with an Ap endo activity of 0.046 is 1.06 times more likely to progress at any moment in time than a glioma with an activity of 0.036, all other things being equal. Note, however, that a difference of 0.01 in activity is relatively small.…”
Section: Resultsmentioning
confidence: 98%
“…In a univariate Cox proportional hazards regression model, with Ap endo activity entered as a continuous variable, the HR increased by a factor of 1.061 for every 0.01 increase in activity {P ϭ 0.013, 95% confidence interval (CI) ϭ [1.013, 1.112]}. 7 Hence, greater Ap endo activity was associated with an increasing hazard for progression (i.e., patients with higher activity had, on average, shorter time to progression). The inverse association between Ap endo activity as a continuous variable and TTP can be illustrated by dividing Ap endo activity into categories and graphically displaying the progression curves within each category: HRs are calculated separately for the 2nd, 3rd, and 4th quartiles of activity relative to the first (i.e., the quartile with the lowest activity).…”
Section: Resultsmentioning
confidence: 99%
“…Despite recent advances in radiation therapy, chemotherapy, and surgical resectioning, the prognosis for patients with malignant glioma is still very poor (1,2). Therefore, the development of a new treatment modality is extremely important.…”
mentioning
confidence: 99%
“…[2][3][4][5][6] Two Phase I studies characterized the toxicity profile and maximum tolerated dose of temozolomide when administered on a 5-day schedule to children. 7,8 Like adult trials, these pediatric studies showed that myelosuppression was the main side effect of temozolomide.…”
mentioning
confidence: 99%